Information Retrieval Systems in Information Chain, Library Institution and Other Information Centers in Information Retrieval - Oya Gürdal Tamdoğan (Türk Kütüphaneciliği)
Elements, that create value in the knowledge production/transfer are the actors that takeparts in the links of ‘information chain'. These actors are ‘authors/re- searchers/scientists' and consequently their products as information resources, ‘publishers'/database producers, ‘distributors'/intermediary organizations and ‘information retrieval systems' which include libraries and other information centers, databases and search engines.